Multiple requirements of PLK1 during mouse oocyte maturation - Solc, Petr; Kitajima, Tomoya S; Yoshida, Shuhei; Brzakova, Adela; Kaido, Masako; Baran, Vladimir; Mayer, Alexandra; Samalova, Pavlina; Motlik, Jan; Ellenberg, Jan (PloS one, 2015)
Polo-like kinase 1 (PLK1) orchestrates multiple events of cell division. Although PLK1 function has been intensively studied in centriole-containing and rapidly cycling somatic cells, much less is known about its function in the meiotic divisions of mammalian oocytes, which arrest for a long period of time in prophase before meiotic resumption and lack centrioles for spindle assembly. Here, using specific small molecule inhibition combined with live mouse oocyte imaging, we comprehensively characterize meiotic PLK1's functions. We show that PLK1 becomes activated at meiotic resumption on microtubule organizing centers (MTOCs) and later at kinetochores. PLK1 is required for efficient meiotic resumption by promoting nuclear envelope breakdown. PLK1 is also needed to recruit centrosomal proteins to acentriolar MTOCs to promote normal spindle formation, as well as for stable kinetochore-microtubule attachment. Consequently, PLK1 inhibition leads to metaphase I arrest with misaligned chromosomes activating the spindle assembly checkpoint (SAC). Unlike in mitosis, the metaphase I arrest is not bypassed by the inactivation of the SAC. We show that PLK1 is required for the full activation of the anaphase promoting complex/cyclosome (APC/C) by promoting the degradation of the APC/C inhibitor EMI1 and is therefore essential for entry into anaphase I. Moreover, our data suggest that PLK1 is required for proper chromosome segregation and the maintenance of chromosome condensation during the meiosis I-II transition, independently of the APC/C. Thus, our results define the meiotic roles of PLK1 in oocytes and reveal interesting differential requirements of PLK1 between mitosis and oocyte meiosis in mammals.
Keywords: Animals; Female; Meiosis; organizační centrum mikrotubulů; Nuclear Envelope; segregace chromozomů; Blotting, Western; ženské pohlaví; Microtubule-Organizing Center; meióza; Oocytes; polo-like kinasa 1; anafázi podporující komplex; kinetochory; Mice; oocyty; Protein Serine-Threonine Kinases; Anaphase-Promoting Complex-Cyclosome; protoonkogenní proteiny; myši; jaderný obal; western blotting; Cell Cycle Proteins; počítačové zpracování obrazu; Polo-Like Kinase 1; Proto-Oncogene Proteins; zvířata; Microscopy, Confocal; konfokální mikroskopie; Chromosome Segregation; proteiny buněčného cyklu; Kinetochores; protein-serin-threoninkinasy; Image Processing, Computer-Assisted